Non-uniform Euler-Bernoulli beams´ natural frequencies - Aya, Hugo; Cano, Ricardo; Zhevandrov, Petr (Ingeniería e Investigación, 2011)
This paper has studied the problem of natural frequencies for Euler-Bernoulli beams having non-uniform cross-section. The numerically-obtained solutions were compared to asymptotic solutions obtained by the Wentzel-Kramers-Brillouin (WKB) method. It was established that WKB formula precision was higher than 3% for high frequencies (≥ 4 mode).